2019
DOI: 10.1017/s1355770x19000196
|View full text |Cite
|
Sign up to set email alerts
|

Middlemen: good for resources and fishermen?

Abstract: This paper studies the role of middlemen in open-access fisheries and how the organization of the supply chains affects resource exploitation and the level and distribution of economic rent. Imperfect competition among middlemen can help ensure that fish stocks are not depleted, which is typically the case in open-access fisheries with competitive markets. Middlemen with market power can also induce higher economic rent for the supply chain in total, but these rents mainly benefit the middlemen. The supply cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Additionally, financiers and middlemen make it convenient for the fishers to market their catch in which they find difficult to do due to their limited education, knowledge in trading and negotiation as well as limited market network (Ruddle, 2011). Thus, they are forced to rely on financial assurance provided by the middlemen during fishing periods, especially in periods with low catches (Tháy et al, 2019). As some of the fishers lack fishing assets like boats, fishing gears due to poverty, this put them at a disadvantage when applying for a loan from a rural or agricultural bank because they lack collateral security (Nazir et al, 2018).…”
Section: Impacts Of Covid-19 and The Challenges Of Policy Restrictionsmentioning
confidence: 99%
“…Additionally, financiers and middlemen make it convenient for the fishers to market their catch in which they find difficult to do due to their limited education, knowledge in trading and negotiation as well as limited market network (Ruddle, 2011). Thus, they are forced to rely on financial assurance provided by the middlemen during fishing periods, especially in periods with low catches (Tháy et al, 2019). As some of the fishers lack fishing assets like boats, fishing gears due to poverty, this put them at a disadvantage when applying for a loan from a rural or agricultural bank because they lack collateral security (Nazir et al, 2018).…”
Section: Impacts Of Covid-19 and The Challenges Of Policy Restrictionsmentioning
confidence: 99%
“…Notably, our pilot study revealed distinct attributes of the Seychelles artisanal fishery value chain likely to impact the future effectiveness of a SSI programme: these merit additional attention. First, there is a high reliance on traders due to their more-flexible pay structure (Figure 1), a common situation in small-scale fisheries (Thủy et al, 2019;Bartkus et al, 2021). Bypassing traders -a common tactic in programmes aimed to increase fisher earnings -would therefore disrupt the existing value chain in Seychelles and would likely face strong resistance, since traders hold significant power in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Although catches gradually increased after the tsunami, many sh stocks remained dwindling and depleted while some dispersed from the area (Sahb 2018). Furthermore, sh scarcity and the manipulation of the sh market by middlemen, lowers the shermen's earnings below 50 percent (personal communication from key informant, November 3, 2020; Tháy et al, 2019), coupled with other critical issues, such as the impact of climate change, environmental pollution, spatial issues, absence of alternative sustainable jobs, and the lack of safety of the shing crew on board. (Esri 2019;Jentoft 2017;Kripa et al 2018).…”
Section: Study Area: Alappad Panchayat In Kerala Indiamentioning
confidence: 99%